Arabic Language Learning Media in Schools Reviewed from the Perspective of Neuroscience/ Media Pembelajaran Bahasa Arab di Sekolah Ditinjau dari Neurosains - Mohamad Jailani (UIN Raden Mas Said Surakarta, 2023)
This research aims to analyze neuroscience-based Arabic language learning media with the goal of facilitating the retention of vocabulary (mufrodat) and proficiency in oral expression (muhadasah). This study is a qualitative literature review. Data is collected through a review of relevant literature from reputable scientific journals and books related to the research. The researcher also supplements secondary data with field data obtained through interviews and observations. The research is conducted at SMK Muhammadiyah 3 Yogyakarta. Data analysis is carried out using content analysis with the addition of data display, reduction, and verification techniques. The results of this research indicate that neuroscience-based Arabic language learning media is effective in meeting the needs of students by simplifying the Arabic learning process, facilitating vocabulary learning (mufrodat) more quickly, and improving reading, writing, listening, and speaking skills (muhadasah). Neuroscience-based Arabic language learning materials emphasize a brain-centered approach to learning Arabic, utilizing the brain's abilities in intellectual growth and tranquility. Learning resources based on neuroscience often take the form of multimedia or instructional videos designed to stimulate the brain as the focal point for mastering Arabic for students. These videos present Arabic content and vocabulary that is easily digestible and suitable for everyday learning, both in the classroom and at home. With the emergence of the COVID-19 pandemic, the transition to online learning has created physical distance between students and teachers, resulting in limited interaction and guidance. Consequently, many students are experiencing difficulties in understanding Arabic language concepts.